Efficiency of Feed Consumption and Rate of Silkworm Respiration (Bombyx mori L.) Mulberry Leaves (Morus sp.) Containing Vitamin B1 (Thiamine) - Masitta Tanjung (International Journal of Ecophysiology, 2021)
The effect of Mulberry (Morus sp.) leave that contain vitamin B1(Thiamine) on the efficiency of feed consumption and respiration rate of silkworm (Bombyx mori L.) had been carried out. This study was complete randomized designed (CRD) by 5 treatments and trireplicated. Each replication consisted of 10 silkworms. The treatmeants were vitamin B1 with concentration of 0; 0,1; 0,2; 0,3 and 0,4mg/100 ml. The results showed that the relative consumption rate increased to the concentration of 0,4mg/100 ml and respiration rate was 0,4mg/100ml (p<0,05). Vitamin B1 had no effect on the relative growth rate, efficiency of convertion of digested food, efficiency of convertion of ingested food and approximate digestibility.